Reassessing the foreign ownership wage premium in Germany - Hartmut Egger; Elke Jahn; Stefan Kornitzky (The World Economy, 2020)
This paper evaluates the effect of foreign takeover on wages of workers in German establishments, using rich linked employer–employee data from 2003 to 2014. To identify a causal effect of foreign takeover, we combine propensity-score matching with a difference-in-difference estimator. We find that a takeover by a foreign investor leads to a wage premium of 4.0 log points in the year after ownership change, which further increases to 6.3 log points 3~years after acquisition. The wage premium is largest for high-skilled workers, which is consistent with three theoretical arguments, namely rent appropriation by managers, technology protection and training on new technology. We also show that the wage premium does not pick up an exporter effect due to a platform investment of the foreign owner, that it takes about 4~years before it fully develops, that it does not vanish after foreign divestment and that the wage increase is specific to foreign acquisition instead of ownership change per se.
Keywords: 330; difference-in-difference estimation; foreign ownership wage premium; impact versus adjustment effects; propensity-score matching